AUTHENTIC LEARNING THROUGH AUDITING SOFTWARE IN LEARNING AUDITING : A MALAYSIAN UNDERGRADUATE PERSPECTIVE - Damien Lung Yau, Lee; Sharon Cheuk, Choy Sheung; Mohd Waliuddin, Mohd Razali; Shamsul Anuar, Abd Rahim (2025)
This paper examines whether auditing software provides students with motivation and interest,learning opportunities, critical thinking, and real-world exposure. The research was conducted125on auditing classes under an undergraduate accounting program in a public university acrossthree semesters from 2022 to 2024. A structured questionnaire was used to assess the student’sauthentic learning experience. Our study providing valuable insights for educators,policymakers, and potential employer by highlighting the experiential authentic learning in aMalaysian university